Nanoporous Au-Sn with solute strain for simultaneously enhanced selectivity and durability during electrochemical CO2 reduction. (15th April 2020) - Lu, Xianglong; Yu, Tianshui; Wang, Hailing; Qian, Lihua; Luo, Ruichun; Liu, Pan; Yu, Yao; Liu, Lin; Lei, Pengxiang; Yuan, Songliu
Abstract: Electrochemical carbon dioxide reduction meditated by metallic catalysts suffers from restricted selectivity and competition from hydrogen evolution, which sensitively depends on ambiguous contributions of alloying and strain state in bimetallic catalysts. Herein, nanoporous Au-Sn (NPAS) containing trace tin solute in Au lattices is delicately designed to convince real strain effect, while eliminating other undesirable factors, such as alloying, crystal facets and surface composition. Compared with nanoporous gold (NPG), the NPAS with a solute strain of ∼2.2 % enables more efficient CO2 -to−CO conversion, with an efficiency as high as 92 % at -0.85 V versus reversible hydrogen electrode ( vs. RHE ), and the high activity can retain for more than 8 h. The combination of HRTEM and surface valence band photoemission spectra reveals that the tensile strain on the surface of 3D nanoporous structure promotes the catalytic activity by shifting up the d -band center and strengthening the adsorption of key intermediate *COOH. A small amount of Sn solute in the nanoporous alloy can prevent ligament coarsening effectively and improve the electrochemical stability.